17.4 STRATIFICATION AND PREDICTION OF REMISSION IN FIRST-EPISODE PSYCHOSIS PATIENTS: THE OPTiMISE COHORT STUDY. (9th April 2019) - Glaichenhaus, Nicolas; Barbosa, Susana; Martinuzzi, Emanuella; Gilet, Cyprien; Jamain, Stéphane; Sommer, Iris; Leucht, Stefan; Dazzan, Paola; McGuire, Philip; Arango, Celso; Diaz-Caneja, Covadonga M; Fleischhacker, Wolfgang; et al.
Abstract: Background: Early response to first-line antipsychotics is associated with positive long-term symptomatic outcome in psychosis. Unfortunately, attempts to identify reliable predictors of treatment response in first-episode psychosis (FEP) patients have not yet been successful. One reason for this could be that FEP patients are heterogeneous in terms of symptoms and underlying disease biological mechanisms, thereby impeding the identification of one-size-fits-all predictors of treatment response. Methods: We have used a two-step hierarchical clustering approach to stratify 325 FEP patients into four subtypes, termed C1A, C1B, C2A and C2B, based on their symptoms assessed using the Positive and Negative Syndrome Scale. After validating our clustering approach on external measures, we then used a regularized logistic regression method to identify biological and clinical variables associated with increased odds of being non-remitters within each subtype. Results: Compared to those from the other subtypes, C1A patients exhibited higher serum levels of several pro-inflammatory cytokines and were the most at risk of being non-remitters when treated with a second-generation antipsychotic drug. In C1A patients, but not in others, lower serum levels of interleukin-15, higher levels of C-X-C motif chemokine 12, previous exposure to cytomegalovirus, use of recreational drugs and a younger age were all associated with higher odds of being non-remitters 4 weeks after treatment. The predictive value of this model was 73%, and its specificity and sensitivity were 45% and 83% respectively. Conclusions: Serum levels of two cytokines combined with three clinical variables predict remission in a subtype of FEP patients.